2015
DOI: 10.1007/s12564-015-9380-y
|View full text |Cite
|
Sign up to set email alerts
|

The increasingly long road to school in rural China: the impacts of education network consolidation on broadly defined schooling distance in Xinfeng County of rural China

Abstract: In the early 2000s, China's Ministry of Education embarked on a program of school mapping restructure (SMR) that involved closing small rural schools and opening up larger centralized schools in towns and county seats.The stated aim of the policy was to improve educational resources and raise the human capital of rural students. Any progress that may have been achieved along these dimensions comes at a price, namely that many children lost the opportunity to learn in their own village schools. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Cai, Chen, and Zhu (2017) found that the compulsory school consolidation program increased educational expenditures, including expenditures on transportation and boarding due to greater distance to school. Zhao and Barakat (2015) found that children from poorer families had difficulties paying for a bus or boarding at school and are more likely to endure longer commutes. Other studies suggest that some poor rural families might be more likely to shoulder costs for boys than girls: research in China suggests that girls' educational attainment has been more susceptible than boys' to poverty (Cherng and Hannum 2013;Liu and Hannum 2017).…”
Section: Impact Of School Consolidationmentioning
confidence: 99%
“…Cai, Chen, and Zhu (2017) found that the compulsory school consolidation program increased educational expenditures, including expenditures on transportation and boarding due to greater distance to school. Zhao and Barakat (2015) found that children from poorer families had difficulties paying for a bus or boarding at school and are more likely to endure longer commutes. Other studies suggest that some poor rural families might be more likely to shoulder costs for boys than girls: research in China suggests that girls' educational attainment has been more susceptible than boys' to poverty (Cherng and Hannum 2013;Liu and Hannum 2017).…”
Section: Impact Of School Consolidationmentioning
confidence: 99%
“…There are a number of examples of financial analysis of changes in costs of schooling post reform (e.g. Pennsylvania School Board Association, 2009; Cooley and Floyd, 2013; Cox and Cox, 2010; Gordon and Knight, 2008; Killeen and Sipple, 2000; Qingyang, 2013; Zhao and Barakat, 2015). Cooley and Floyd (2013) studied 20 consolidated districts in Texas (USA) and found that post-consolidation there was no financial saving on a per-pupil basis (when compared with non-consolidated schools).…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…The more hidden cost is, however, for students who experience increased travel times (Qingyang, 2013). Zhao and Barakat (2015) calculated from their analysis of rural school consolidation that the addition travel time can be up to 130 min per week based on their study of 986 students in a province in China. The average travel time increase was 75 min per week.…”
Section: Overview Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In this process of merging, elementary schools in poor mountainous areas are the most heavily and profoundly affected, resulting in greater distance to schools for many rural students and a small number of urban students. Many children have lost the opportunity to study in their rural schools [ 5 ]. The school mapping restructure plan has brought great inconvenience to rural children and parents.…”
Section: Introductionmentioning
confidence: 99%